The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1155/2020/1763142
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Special‐Shaped Concrete‐Filled Square Steel Tube Column under Axial Compression

Abstract: The axial compressive performance of novel L-shaped and T-shaped concrete-filled square steel tube (L/T-CFSST) column was assessed in this study. Ten L/T-CFSST columns were tested to failure under axial load. The experimental data were used to determine various failure modes, bearing capacities, and load-displacement curves. The test parameters included the section form, steel tube thickness, steel yield strength, and slenderness ratio. The axial compressive performance of the L/T-CFSST column proved favorable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, the hoop coefficient, ξ, of the specimen decreases with the increase of the strength of concrete, which leads to the decrease of the restraint effect of multi-cavity steel tube on concrete. This further accelerates the decline rate of bearing capacity and reduces the ductility of the specimen (Wang, Zhou, et al, 2020).…”
Section: Concrete Strengthmentioning
confidence: 99%
“…On the other hand, the hoop coefficient, ξ, of the specimen decreases with the increase of the strength of concrete, which leads to the decrease of the restraint effect of multi-cavity steel tube on concrete. This further accelerates the decline rate of bearing capacity and reduces the ductility of the specimen (Wang, Zhou, et al, 2020).…”
Section: Concrete Strengthmentioning
confidence: 99%
“…Yang et al [28] researched the seismic behavior of four-legged square CFST latticed members under lateral cyclic loading and revealed that the fourlegged square CFST latticed specimens outperformed hollow steel ones in terms of hysteretic behavior. Wang et al [29] experimentally investigated the axial compressive performance of novel L-shaped and T-shaped concretefilled square steel tube (L/T-CFSST) columns and established formulae to calculate the axial compressive strength and stability bearing capacity of the L/T-CFSST columns accordingly. Shariati et al [30] presented a numerical investigation into the behavior of built-up concrete-filled steel tube columns under axial compression and indicated that the raise of concrete strength with greater cross section led to a higher load bearing capacity compared to the steel tube thickness increment.…”
Section: Introductionmentioning
confidence: 99%
“…e confinement effect of external steel pipe changes the concrete from two-way stress state to three-way stress state, which can improve the compressive properties of concrete. e internal concrete can improve the buckling of steel pipe and ensure the full play of material properties [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete-filled steel pipe has been widely used in ground buildings due to its high strength and good ductility [9,[11][12][13][14][15][16]. In recent years, some scholars have begun to propose the introduction of concrete-filled steel pipe into coal mine roadway support.…”
Section: Introductionmentioning
confidence: 99%